Palaeopathology in Egypt and Nubia : a century in review - Metcalfe, Ryan,; Cockitt, Jenefer,; David, A. Rosalie (Archaeopress Egyptology ;, 2014)
The study of human remains from ancient Egypt and Nubia has captured the imagination of many people for generations, giving rise to the discipline of palaeopathology and fostering bioarchaeological research. This book contains 16 papers that cover material presented at a workshop entitled 'Palaeopathology in Egypt and Nubia: A Century in Review,' held at the Natural History Museum, London (August 29-30, 2012), which formed part of a three-year research project, 'Sir Grafton Elliot Smith: Palaeopathology and the Archaeological Survey of Nubia.' The papers explore the subject of palaeopathology from its beginnings in the early 1900s through to current research themes and the impact of technological development in the field.